Comparative study of different milk feeding systems in orphan kids - RAMGOVIND, RAMGOVIND; JOSHI, H C; PATEL, B H M; VERMA, M R; FAHIM, A H; DUTT, T (The Indian Journal of Animal Sciences, 2012)
The present study was conducted to test a group milk feeding device developed by Farm machinery and Power Workshop, IVRI for feeding orphan kids. Ten suckling kids were placed in natural suckling group (T1). The kids born which were not accepted by dam were considered as orphan. Among orphan kids, 10 kids each were kept in individual bottle feeding (T2) and group milk feeder (GMF) T3 group. The experiment was conducted for 90 days. Body weight gain, time and labour required under different feeding systems were recorded. The average body weights at the end of the experiment for the corresponding treatment groups were 11.230, 6.69±0.53 and 10.77±0.58 kg respectively. The body weight gain in T2 and T3 did not differ significantly in first month but differed significantly (P